Interlinking dementia in Parkinson’s disease: Nutritional correlates of body composition - Schelp, Arthur Oscar [UNESP]; Komuro, Jéssica Emy; Corrente, José Eduardo; Papini, Silvia Justina (Elsevier, 2020)
Little evidence showed that body composition has a primary role in the development of dementia in Parkinson’s disease (PD). However, several studies indicated that metabolic and nutritional dysfunctions have a relevant influence on disease outcome. The confluence of several disturbances, including disruption in fat and glucose metabolism, with nutritional component abnormalities, could be a crucial event when associated with dopamine depletion in the striatum of patients with PD. It was discussed that there may be a relationship between decreased insulin resistance and cholesterol lower levels as a possible risk factor to dementia associated with PD (PDD). The possibility that nutritional habits, metabolic disturbances, and dopamine depletion in the striatum could have a synergic action on PDD is taken into consideration. Thus, future studies should establish dietary measures for elderly patients with PD, associated or not with dementia.
Keywords: Body composition; Fat metabolism; Glucose; Parkinson’s dementia diet; Parkinson’s disease; Parkinson’s nutrition